Antisense RNA Design, Delivery, and Analysis - Arechavala-Gomeza, Virginia; Garanto, Alejandro (Methods in Molecular Biology,, 2022)
This open access volume gathers a variety of models, delivery systems, and approaches that can be used to assess RNA technology for exploiting antisense as a therapeutic intervention. Beginning with a section on the design of antisense technology and their delivery, the book continues by covering model systems developed to evaluate efficacy, both in vivo and in vitro, as well as methods to evaluate preclinically the toxicity associated with these new potential drugs, and intellectual property considerations. Written for the highly successful Methods in Molecular Biology series, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Authoritative and practical, Antisense RNA Design, Delivery, and Analysis provides basic knowledge and a large collection of methods to facilitate the workof newcomers to this vibrant and expanding field. This book was conceived thanks to the network DARTER (Delivery of Antisense RNA Therapeutics). DARTER is funded by the EU Cooperation of Science and Technology (COST), which aims to enhance interaction and collaborations between researchers in Europe and other countries.